Chemical composition and antifungal activities of aromatic water of Zataria multiflora Boiss - Ali Arabi Monfared; Maryam yazdanpanah; Zahra Zareshahrabadi; Keyvan Pakshir; Mehdi Ghahartars; Davood Mehrabani; Samira Yazdanpanah; Aida Iraji; Kamiar Zomorodian (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: In Iranian culture, aromatic waters harboring a slight amount of essential oil have been popularly used for many years as a pleasant non-alcoholic drink with various medicinal properties.In this study, chemical composition of Zataria multiflora Boiss. (ZM) aromatic water was determined and its in vitro and in vivo antifungal properties were investigated.Materials and Methods: Chemical composition of the essential oil extracted from aromatic water (AW) of ZM was analyzed by Gas chromatography and gas chromatography-mass spectrometry (GC-MS). The antimicrobial activity of the AW against Candida species was determined by broth micro-dilution methods. Additionally, biofilm formation inhibition and antioxidant activity of the AW were measured using XTT reduction and DPPH methods, respectively. Antifungal activities of the AW in the prevention and/or treatment of gastrointestinal (GI) candidiasis in animal models were also evaluated.Results: The GC-MS analysis revealed that the major constituents of ZM AW were Carvacrol (46.56%) and Thymol (40.67%). The ZM AW inhibited the growth and biofilm formation of Candida species in the range of 0.25-0.5 V/V. Moreover, ZM AW significantly decreased Candida colonization in therapeutic groups (P<0.05). Conclusion: Given the wide therapeutic potential of ZM AW, including antifungal and antioxidant activities, it might be possible to use it in the management of mucocutaneous or alimentary candidiasis.